THE EFFECTS OF CONTENT AND INFLUENCER MARKETING ON PURCHASING DECISIONS OF FASHION ERIGO COMPANY - H.P, Yodi; Widyastuti S; Noor, L.S (Dinasti Publisher, 2020)
This study aims to study content marketing and influence marketing on the purchasing decisions mediated by consumer behavior. The population used in this study were consumers from the Erigo Company. The sampling technique used purposive sampling with the number of samples obtained as many as 100 respondents. The analysis technique used in this study is the path analysis method. The test results show that content marketing has a direct influence and contribution to consumer behavior, the influence of marketing in the same direction and contribution to marketing behavior, content marketing has a direct and contributing to purchasing decision, marketing influence in the same direction and contributes to purchases, consumer behavior has a same direction and contribution to purchasing decisions. The influence of content marketing proved to be in the same direction and has a significant contribution to purchasing decisions through consumer behavior, the influence of influencer marketing proved to be in the same direction and has a significant contribution to purchasing decisions through consumer behavior. The results of this test also show a measure of the indirect effect of marketing content and the effect on purchasing decisions through behavior smaller compared to the influence of product differences and the effect of marketing on purchasing decisions directly.